Surgical Removal of Circumferentially Leaked Polymethyl Methacrylate in the Epidural Space of the Thoracic Spine after Percutaneous Vertebroplasty - Kita, Kenichiro; Takata, Yoichiro; Higashino, Kosaku; Yamashita, Kazuta; Tezuka, Fumitake; Sakai, Toshinori; Nagamachi, Akihiro; Sairyo, Koichi (The Surgery Journal, 2017)
Background The major complication of percutaneous vertebroplasty (PVP) using polymethyl methacrylate (PMMA) is epidural leakage of PMMA that damages the spinal cord.Methods This is a case report.Result A 77-year-old man presented to our institution with a 6-month history of muscle weakness and an intolerable burning sensation of both lower limbs after PVP with PMMA for thoracic compression fracture at T7 at another hospital. His past medical history was significant for hypertension. He had no history of smoking and alcohol. Computed tomography revealed massive leakage of PMMA into the T6 and T7 spinal canal circumferentially surrounding the spinal cord that caused marked encroachment of the thecal sac. Magnetic resonance images revealed cord compression and intramedullary signal change from T6 to T7 level. After we verified that the leaked PMMA could be easily detached from the dura mater in the cadaveric lumbar spine, surgical decompression and removal of epidural PMMA was performed. The leaked PMMA was carefully thinned down with a high-speed diamond burr. Eight pieces of PMMA were detached from the dura mater easily without causing a dural tear. No neurologic deterioration was observed in the postoperative period. The burning sensation resolved, but the muscle weakness remained unchanged. One and a half years postoperatively, the muscle weakness has improved to ⅘ on the manual muscle strength test, but he could not walk without an aid because of spasticity.Conclusion This report demonstrates the catastrophic epidural extrusion of PMMA following PVP. Extravasated PMMA can be removed through a working space created by means of laminectomy and subtraction of the affected pedicle. Spine surgeons should recognize the possible neurologic complications of PVP and be prepared to treat them using suitable approaches.
Keywords: percutaneous vertebroplasty; cement leakage; neurologic deficit; surgical removal